2006
DOI: 10.1177/1069072706288928
|View full text |Cite
|
Sign up to set email alerts
|

Need, Awareness, and Use of Career Services for College Students

Abstract: This study examined whether university students were psychologically distressed or had difficulties with career decisions to indicate whether they needed career services, whether they were aware of the services offered by the campus counseling and career services, and finally, whether they had used the services. Findings indicated that students indicated difficulties with career decisions, high levels of psychological distress, and low levels of psychological well-being and that about half of students were awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 30 publications
2
81
0
6
Order By: Relevance
“…The study confirmed Krieshok's (1998) view that decision making is not simply a linear, rational process but, rather, a complex process often involving subconscious motivations. The findings also reveal that career indecision may be brought about by (conscious and subconscious) emotional problems (Di Fabio and Kenny 2011;Fouad et al 2006). Hartung The present study results are also consistent with those of Braunstein-Bercovitz, Benjamin, Asor and Lev (2012) and Kim, Kang, Cho and Lee (2011), who established a significantly positive correlation between the quality of the relationship between clients and their parents and career indecision.…”
Section: Discussionmentioning
confidence: 84%
“…The study confirmed Krieshok's (1998) view that decision making is not simply a linear, rational process but, rather, a complex process often involving subconscious motivations. The findings also reveal that career indecision may be brought about by (conscious and subconscious) emotional problems (Di Fabio and Kenny 2011;Fouad et al 2006). Hartung The present study results are also consistent with those of Braunstein-Bercovitz, Benjamin, Asor and Lev (2012) and Kim, Kang, Cho and Lee (2011), who established a significantly positive correlation between the quality of the relationship between clients and their parents and career indecision.…”
Section: Discussionmentioning
confidence: 84%
“…Research in the United States has found a positive correlation between emotions and career decision-making, including greater capacity to manage one's own emotional response to this process (Emmerling&Cherniss, 2003) as well as trust in one's capacity to confront career decision-making tasks (Brown,George, & Smith, 2003). Further, difficulties in career decision making are found to be associated with psychological distress and low levels of well-being (Fouad et al, 2006). The current study will focus on the latter perspective, that is, how one's emotional well-being is relevant to career choice.…”
Section: Career Decision-makingmentioning
confidence: 99%
“…Dans le champ de l'orientation professionnelle, cette question apparaît peu documentée. Fouad et al (2006) ont relevé un fort décalage entre les besoins exprimés et l'utilisation effective des services sur un campus universitaire; par exemple, si 51,2% des participants déclarent ressentir le besoin d'un accompagnement individuel, seuls 6,1% y ont effectivement recours. Au vu de ces différents résultats, se pose la question de savoir comment les services sont utilisés, qui s'y engage et pour quel motif; finalement, la question centrale est de cerner quels sont les déterminants de l'entrée en consultation d'orientation professionnelle.…”
Section: Introductionunclassified
“…Kahn, Wood et Wiesen (1999) ont montré que la majorité des étudiants de leur échantillon connaissent l'existence du centre de counseling, mais ne savent pas quels services y sont dispensés. Fouad et al (2006) constatent également qu'il existe une différence relativement …”
unclassified